Determining Soil Bulk Density for Carbon Stock Calculations: A Systematic Method Comparison. Issue 3 (24th June 2016) - Walter, Katja; Don, Axel; Tiemeyer, Bärbel; Freibauer, Annette
Abstract : Core Ideas: Little is known about the methodological errors of bulk density quantification. Soil probes are easy to handle, but systematic methods comparisons are lacking. We compared methods among three soil ring types and three soil probe types at four sites. Accurate and effective determination of soil bulk density (BD) is needed to monitor soil organic C (SOC) stocks and SOC stock changes. However, BD measurements are often lacking in soil inventories and BD is estimated by pedotransfer functions with substantial uncertainty. In a systematic method comparison, we evaluated different methods for BD determination in the field by comparing the performance of MINI (5 cm 3 ) and BIG (250 cm 3 ) sample rings and of three driving hammer probes differing in diameter, material, and extraction method. Bulk density determined with 100‐cm 3 sample rings was defined as the reference method (REF). All methods were tested at five depth increments in nine subplots at four sites with differing soil texture and SOC content. All methods determined BD in the depth increments with low systematic error (8% for probes and 2% for sample rings). The random error of the probe samples was, on average, 50% higher than that of the ring samples when the cores of the probes were adequately corrected for compaction or stretching. The BD was significantly overestimated (by 2%) when determined with MINI rings, and the variation in BD was not reduced with BIG sample rings rather than the smaller REF sample rings. The performance of the driving hammer technique varied widely among probe types and sites. The sheath probe had the smallest systematic error of all probes tested and is recommended for soil inventories. All methods for estimating BD had smaller errors than pedotransfer functions.